Comparison of cardiac troponin T and N-terminal pro-B-type natriuretic peptide between fetuses with hemoglobin Bart's disease and nonanemic fetuses - Tongprasert,F. (John Wiley and Sons Ltd, 2015)
Objective: The objective of this study was to compare the levels of fetal serum cardiac troponin T (cTnT), representing cardiac injury, and N-terminal pro-B-type natriuretic peptide (nt-proBNP), representing cardiac volume overload, between fetuses affected and not affected by hemoglobin (Hb) Bart's disease, as well as between anemic and nonanemic fetuses. Methods: One hundred fourteen pregnancies at risk for fetal Hb Bart's disease scheduled for cordocentesis at 18 to 22weeks were recruited into the study. Fetal blood was collected to test for cTnT, nt-proBNP and Hb levels as well as Hb typing. Results: Serum nt-proBNP was significantly higher in Hb Bart's fetuses (24 cases) than in unaffected fetuses (63 cases), whereas cTnT was significantly lower in the affected group than in the unaffected group. The serum nt-proBNP levels significantly increased with the degree of fetal anemia; cTnT levels decreased in fetuses with high degree of anemia. Conclusions: At mid-pregnancy, nt-proBNP was significantly higher in fetuses with Hb Bart's disease than in nonanemic fetuses; cTnT was significantly lower in anemic than in normal fetuses. This study suggests that cardiomegaly from fetal anemia in early gestation is not associated with fetal cardiac injury or myocardial dysfunction but presents as cardiac volume overload from a compensatory process to maintain adequate tissue oxygenation. © 2014 John Wiley & Sons, Ltd.